Application of Social Constructivism in Medical Education - Kim, Youngjon (Korean Medical Education Review, 2024)
The purpose of this study is to discuss the main principles and concepts of social constructivism, examine the literature on the application of social constructivism in medical education, and explore the meaning and limitations of the utilization of social constructivism with learning theory. A literature search was carried out in two stages, utilizing PubMed, CINAHL and Education Source databases. The primary search included both fields (social constructivism AND medical education), while the secondary search was performed by subject (Vygotsky or ZPD or zone of proximal development or scaffolding AND medical education). A total of 96 papers were found through the primary and secondary searches, and after reviewing the abstracts of all 96 papers, 41 papers were deemed suitable for research purposes. In medical education, social constructivism is applied in areas such as (1) social and cultural behaviors (hidden curriculum), (2) social construct of “meaning” (dialogue and discourse), (3) learner’s identity transformation (expert), and (4) instructional intervention (ZPD and scaffolding). Social constructivism has provided many ideas to explore in terms of the composition of knowledge in the sociocultural context of health care, but it has not demonstrated an explicit instructional method or educational effects.